Abrasamento induzido por nicotina: estudo da progressão temporal e influência do sexo nas alterações neuroquímicas em ratos periadolescentes - Gomes, Patrícia Xavier Lima (2016)
Kindling classically was used as an experimental model of temporal lobe epilepsy. In the last decades, it has also been used to conceptualize the general mechanisms involved in the progression of a wide range of neuropsychiatric disorders. Kindling model can be induced by subthreshold electrical and chemical stimulus. Recently, nicotine (NIC)-induced kindling was pharmacologically and histologically characterized, opening perspectives to better understand the neurochemical and behavioral effects of NIC in the neuroprogressive course involved in kindling phenomenon. In this context, relevant sex-dependent effects have been attributed in neurobiology of NIC-induced kindling, whose mechanisms has not been fully clarified. Therefore, the present study aimed to investigate the temporal progression and influence of sex of neurochemical alterations induced by NIC kindling model in periadolescent rats. Male and female Wistar rats (aging 35-37 days) received repeated intraperitoneal NIC 2.0 mg / kg administration, from Monday to Friday. Control animals received saline administration. The seizures were evaluated by Racine Scale on the days 1, 10, 19, 22, 24 and 25 NIC administrations. Thirty minutes after NIC administration on the days 1, 10 and 19 for females and 1, 10 and 25 for males, the animals were euthanized and their brain areas, striatum (ST) and hippocampus (HC) were dissected for neurochemical analysis and immunofluorescence. Female animals showed greater susceptibility to the development of kindling when compared to males, presenting stage 5 of seizures on 19th day of NIC administration, while males presented the same stage on 24th day. In relation to animal mortality, females were more vulnerable to the NIC toxic effects, presenting 75% of mortality. Regarding plasma levels of 17β-estradiol, there were no differences between males and females treated with NIC or saline. The content of dopamine (DA) and its metabolites, DOPAC and HVA, in ST of males were higher on the 1st day of NIC administration compared to controls, followed by reduction on the kindling progression course. In females, DOPAC levels was reduced on the 1st day of NIC treatment, compared to controls, however it increased in the kindling. Contrarily, HVA levels reduced in the kindling. In HC, DA levels and its metabolites were lower in male animals on the 1st day of NIC treatment compared to controls, and remaining reduced in the kindling. Regarding NE content, it was higher in female HC when compared to males in kindling model. Similarly, the activity of the acetylcholinesterase enzyme and the immunoexpression of p-NR1 and p-CREB were higher in female NIC-kindling in ST related to males. Finally, NIC-kindling females presented higher BDNF levels in ST compared to NIC-kindling males and control females. Therefore, the present study demonstrated that female animals are more vulnerable to kindling phenomenon. Further, based on our results, we suggested that this differential vulnerability was due to an increase in neuronal excitability and consequently cell damage during the kindling temporal progression.